Leadership dynamics, administrative efficiency, leadership abilities & approaches among department heads in Ifugao Province, Philippines: Implications for effective governance - Hernando, Fernando G.; Malinao, Client William M. (Masyarakat, Kebudayaan dan Politik, 2025)
The efficacy of government is mainly dependent on public service leaders, who are top civil officials who oversee and enhance key government operations. They convert political direction into programs and policies that maintain citizens’ economic productivity, safety, and well-being. As such, this study determines the administrative capabilities, the level of program implementation, leadership qualities, and the styles of the department heads in the 11 municipalities in Ifugao Province. Using a descriptive-comparative research design, data were gathered from the 106 department heads and validated by the 92 elected officials and 449 employees. Using descriptive statistics and an F-test, findings revealed that the department heads are perceived to be capable of performing core management functions. Regarding program implementation, respondents concurred on moderately effective program execution. All groups agreed that the office heads possess the qualities of a leader who envisions the future and inspires members. On the leadership styles, the participative style of leadership, which ushered in the inclusion of employees in decision-making, was agreed upon by all respondents. The perceptions of the three groups were not significantly different regarding management functions, leadership qualities, and leadership styles of the department heads. Results map the strengths and gaps in the department heads’ leadership styles and administrative capability, outlining helpful information for policy formulation and capacity-building initiatives.